2019
DOI: 10.1016/j.celrep.2019.01.115
|View full text |Cite
|
Sign up to set email alerts
|

Signal Integration by Shadow Enhancers and Enhancer Duplications Varies across the Drosophila Embryo

Abstract: SUMMARY Transcription of developmental genes is controlled by multiple enhancers. Frequently, more than one enhancer can activate transcription from the same promoter in the same cells. How is regulatory information from multiple enhancers combined to determine the overall expression output? We measure nascent transcription driven by a pair of shadow enhancers, each enhancer of the pair separately, and each duplicated, using live imaging in Drosophila embryos. This set of constructs allows us to quantify the i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 60 publications
(127 reference statements)
4
45
0
Order By: Relevance
“…These concerns apply mostly to questions of the additivity of the Bra Proximal and Distal enhancers. Although they appear to be slightly super-additive in our experiments, this was not our major focus and a more elaborate set of controls akin to Scholes et al (2019) would be needed to fully explore this question. We have not, for example, excluded the possibility that the region between the Proximal and Distal enhancer elements might contain relevant transcription factor binding sites.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…These concerns apply mostly to questions of the additivity of the Bra Proximal and Distal enhancers. Although they appear to be slightly super-additive in our experiments, this was not our major focus and a more elaborate set of controls akin to Scholes et al (2019) would be needed to fully explore this question. We have not, for example, excluded the possibility that the region between the Proximal and Distal enhancer elements might contain relevant transcription factor binding sites.…”
Section: Discussionmentioning
confidence: 92%
“…Distributed enhancer pairs have been found to function in sub-additive, additive and super-additive regimes (Bothma et al, 2015), although sub-additive and additive relationships have been most common in the limited number of cases where this has been addressed. Scholes et al (2019) recently found that the additivity of different combinations of Krüppel enhancers is not uniform as a function of the different concentrations of upstream activators present at different AP positions in the early Drosophila embryo. These particular enhancers are thought to respond to different combinations of upstream transcription factors, but it is also possible that distributed enhancers might have quantitatively different responses to the same upstream regulators.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of interaction is consistent with our finding that super-multiplicative gene expression responses are associated with nearby super-additive ATAC-seq peaks. Sub-additive transcriptional responses have been proposed to reflect saturation of cis-regulatory elements (Bothma et al, 2015;Scholes et al, 2019) . Saturated cis-regulatory elements would in principle show up as sub-additive ATAC-seq peaks in our analysis, but we did not observe an increase in sub-additive peaks near genes with sub-additive combined responses (with the exception of a small increase at high dose).…”
Section: Discussionmentioning
confidence: 99%
“…12enhancer-promoter loops(Furlong & Levine, 2018), recent studies suggest that enhancer-promoter 13 distance can indeed have an effect on expression levels(Carleton et al, 2017;Scholes et al, 2019). 14 Future studies will show whether the distance between enhancer and promoter can also affect the timing 15 of enhancer activity in a developmental setup.…”
mentioning
confidence: 99%